Sexual therapy in Croatia: taking the first steps - Arbanas, Goran (Array, 2008)
Objective Although one quarter of men and one third of women in Croatia have experienced a sexual difficulty at least once, sexual therapy was unknown in Croatia before 2004, when the first professional training program was started. We analyze the structure of sexual health difficulties reported in e-mail queries to three specialized Croatian Q&A websites during the 2004- 2007 period. Design and methods We analyzed 246 individual e-mail queries about personal or partner's sexual health problems. Results The majority of male clients (47% of the sample) described their own problem(s) ; only 18% reported their partner's problem(s). In contrast, 38% of female clients queried in regard to their partner's problem. The most prevalent problems in men were erectile difficulties (35%), rapid ejaculation (23%), hypoactive sexual desire (15%), and delayed ejaculation (13%). Paraphilias (4%) and sexual orientation and gender identity issues (3%) were mentioned less often. In women, the most frequent problems were anorgasmia (41%) and hypoactive sexual desire (25%). Dyspareunia (7%), arousal difficulties (5%), vaginisms (5%), and sexual aversion (4%) were sporadically reported. While younger men (age group 17-30) most often reported problems with erection and rapid (or sometimes delayed) ejaculation, middle-aged and older men (age group 31-60) queried mostly about their erectile problems. No comparable difference was found among women. Conclusion Erectile and ejaculation difficulties in men, and anorgasmia and hypoactive sexual desire in women were the most often reported sexual difficulties. Several sociocultural factors seem to be associated with the findings.